East Urals Radioactive Trace: Dose-dependent functional-metabolic effects in the myocardium of the pygmy wood mouse (Apodemus uralensis) taking into account population size. (September 2017) - Orekhova, Nataĺya A.; Modorov, Makar V.
Abstract: The population dynamics, radiometric data and biochemical parameters (concentrations of total lipids, proteins, DNA and RNA, activity of succinate dehydrogenase, glucose phosphate isomerase and catalase, as well as lipid peroxidation level) in the myocardium of the pygmy wood mouse ( Apodemus uralensis Pall., 1811) inhabiting the area of the East Urals Radioactive Trace (EURT) were analyzed. The functional-metabolic radiation effects as a result external and internal exposure to 137 Cs and 90 Sr (unweighted total dose rate 0.04–0.5 mGy/day) are characterized by a reduction in lipid catabolism, mitochondrial oxidation and antioxidant defense, as well as the activation of anaerobic glycolysis as well as the protein-synthesizing and genetic apparatus. The data indicate the low efficiency of cell energy production and allow us to state that compensatory myocardial hypertrophy can improve myocardial contractile function. The level of the functional-metabolic response in pygmy wood mice in the EURT area increased with increasing whole-body radiation dose rate and was more pronounced with a large pygmy wood mouse population size. The harmful effects (cardiac decompensation stage) of synergies resulting from non-radiation and radiation factors manifest after population abundance above 30 ind./100 trap-day and a radiation burden above 0.1 mGy/day.